Impact of Streetscape Attributes on Walkability and Urban Pedestrian Experience, A Case of Swayambhu Marg - Shrestha, Sophiya; Bajracharya, Ashim Ratna (Journal of Engineering Issues and Solutions, 2026)
Walkability refers to how friendly and accessible an area is for walking. It encompasses a range of physical and environmental factors such as Pedestrian Infrastructure Robustness, Comfort, Safety and Functionality, that influence whether people are likely to choose walking as mode of transport. The urban pedestrian experience describes how individuals perceive and interact with the urban environment while walking. A positive pedestrian experience encourages walking, fosters community engagement and enhances overall quality of life in urban settings. The research analyzes degree of perceived walkability on micro scale i.e. in streetscape attributes. The study utilizes multifaceted approach, combining objective study i.e. observation, Pedestrian Environment Data Scan with subjective study survey was conducted along with cognitive testing. Due to inadequate sidewalks and inconsistent streetscape elements the pedestrians experience is often fragmented in case of Swayambhu Marg. The results show that the street has lower functionality score indicating that components of functionality should be prioritized to improve walkability in the street. These findings offer actionable insights for designers and urban planners to improve walkability and enhance pedestrian experience in urban areas.